Améleorer les résultets en matière de santé, nutrition et démegraphie en afrique subsaharienne : (Banque Mondiale, 2005)
This book takes an in-depth look at health, nutrition, and population (HNP) challenges faced by Sub-Saharan Africa, particularly how disease, malnutrition, and high fertility affect poverty reduction